Процена метода анализе и интерференције коагулационих анализатора СИСМЕКС ЦН-6000 и СТАГО СТА-Р - orhan, seren; işbilen, Elif (Journal of Medical Biochemistry, 2025)
AbstractObjective: The aim of this study was to compare the analytical methods of STAGO STA-R and SYSMEX CN-6000 coagulation analyzers. Also, to evaluate the effects of lipemia and hemolysis interferences on the methods. STA-R detects clotting using an electromechanical method, while the CN-6000 detects clotting using an optical method. We compared the activated partial thromboplastin time (APTT), prothrombin time (PT), Fibrinogen (FBG)  and D-Dimer results of both analyzers. We also examined the effects of hemolysis and lipemia on PT (INR), APTT and FBG analyses.Methods: Randomly selected blood samples from Gaziantep University Hospital patients were used. PT (INR), APTT, FBG, D-Dimer analysis was performed using both analyzers. Precision, comparability and interference studies were performed in the study. Studies were performed according to CLSI documents (H21-A5, EP15-A3, EP07-Ed3)Results:  In the precision study, all % CV values were within the acceptable limits of between-subject biologic variation criteria for hemostasis tests. The correlation coefficients of PT (INR), APTT, FBG, D-Dimer results between the two devices were found to be r=0.982 (p